Efficacy of micafungin, a candin antifungal agent, in guinea pig models of disseminated candidiasis and pulmonary aspergillosis - Nakai, Toru; Hatano, Kazuo; Wakai, Yoshimi; Matsumoto, Satoru; Maki, Katsuyuki; Ikeda, Fumiaki (Japanese Journal of Chemotherapy, 2006)
The efficacy of micafungin (MCFG) and voriconazole (VRCZ) was evaluated in guinea pig models of disseminated candidiasis and pulmonary aspergillosis. MCFG and VRCZ were administered twice daily for 9 days starting at 2-4 hour after infection by subcutaneous injection and oral administration, respectively. MCFG and VRCZ significantly prolonged the survival of guinea pigs infected intravenously with Candida albicans at doses of 0.32 and 1mg/kg, respectively (p<0.05). MCFG and VRCZ significantly prolonged the survival of guinea pigs infected intratracheally with Aspergillus fumigatus at doses of 1.00 and 3.2mg/kg, respectively (p<0.01). These results supported the efficacy of clinical doses of MCFG and VRCZ in treating disseminated candidiasis and pulmonary aspergillosis.